Vulnerability assessment: A comparison of three different city sizes in the coastal area of Central Java, Indonesia - Handayani, Wiwandari; Rudiarto, Iwan; Setyono, Jawoto Sih; Chigbu, Uchendu Eugene; Sukmawati, Annisa Mu'awanah (Advances in climate change research, 2017)
Considering the importance of connecting urbanization phenomena and vulnerability assessments, this paper aims to explore vulnerability assessment in three different city sizes in the northern coast of Central Java province of Indonesia. It compares the vulnerability levels of the three cities based on their sizes (that is, levels of urbanization). It uses the most current secondary data from the lowest administrative levels,called as kelurahan (urban village), for its assessment. There are two indexes used to indicate their vulnerability levels, namely exposure and sensitivity index (ESI) and adaptive capacity index (ACI). By combining the ESI and ACI, the study found that the kelurahans in Tegal (the medium sized city) have similar vulnerability levels. The kelurahans in Semarang (as the big city) have more combination of vulnerability levelsdindicating that the city has various sensitivity, exposure, as well as adaptive capacity among its kelurahans. In Lasem (the small sized city), due to limitations imposed by adaptationdmostly because of lack of public services and high dependency on primary economic sectorsdall of its kelurahans were found to be vulnerable. The study therefore concluded that the bigger a city is, the more the different areas of that city will have varying levels of vulnerability, leading to a high propensity of vulnerability among its inhabitants. On the other hand, the smaller a city is, the less capacity it will have in reducing its emerging vulnerability challenges.